Penerapan Model Teams Games Tournament dengan Video Pembelajaran untuk Meningkatkan Prestasi Belajar dan Kolaborasi Peserta Didik pada Mata Pelajaran Matematika Materi KPK FPB Kelas IV SD Negeri Kleco 1 Surakarta - Adliya, Nafa; Novitasari, Meggy; Suryanti, Suryanti (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
This research is a classroom action research that aims to evaluate the impact of implementing the Team Games Tournament (TGT) learning model on increasing learning achievement and collaboration between students. This research was carried out in class IVA at SDN Kleco 1 Surakarta in the odd semester of the 2023/2024 academic year with a total of 29 students. This research was conducted in two cycles. The data collection methods in this research are test, questionnaire and documentation methods. The test method is used to determine student test results. The questionnaire method is used to observe student collaboration. Documentation method for student test result data, observation sheets and modules. The data analysis techniques used include quantitative and qualitative approaches, by assessing the success of the research based on the increase in average learning achievement and the level of collaboration between students in each cycle. The results of the research showed that student collaboration at the pre-cycle stage achieved results of 20.68% with 0% of students or none being able to collaborate very well. Then the first cycle experienced an increase, namely obtaining learning completeness of 68.9% with 28 % of students are able to collaborate very well. Cycle II achieved 100% learning completeness with 62% of students able to collaborate very well. Therefore, it can be concluded that using the Team Games Tournament (TGT) learning model with the help of learning videos can improve learning achievement and collaboration between students.